2016
DOI: 10.1002/anie.201509084
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for the Synthesis of Binary Tungsten Iodides

Abstract: The preparation of tungsten iodides in large quantities is a challenge because these compounds are not accessible using an easy synthesis method. A new, remarkably efficient route is based on a halide exchange reaction between WCl6 and SiI4. The reaction proceeds at moderate temperatures in a closed glass vessel. The new compounds W3I12 (W3I8 ⋅2 I2) and W3I9 (W3I8 ⋅½I2) containing the novel [W3I8] cluster are formed at 120 and 150 °C, and remain stable in air. W3I12 is an excellent starting material for the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…[14][15][16] A 2 [W 6 I 14 ] compounds with A = alkaline metal are usually obtained from solid-state reactions of mixtures of a binary iodide (e.g. W 3 I 12 [17] or W 6 I 12 [18] ) and AI in appropriate proportions at elevated temperatures. At this point of state, it is likely to assume that alkaline earth (AE) compounds with the formula AE[W 6 I 14 ] can be prepared by the same way of synthesis, as testified in this report.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] A 2 [W 6 I 14 ] compounds with A = alkaline metal are usually obtained from solid-state reactions of mixtures of a binary iodide (e.g. W 3 I 12 [17] or W 6 I 12 [18] ) and AI in appropriate proportions at elevated temperatures. At this point of state, it is likely to assume that alkaline earth (AE) compounds with the formula AE[W 6 I 14 ] can be prepared by the same way of synthesis, as testified in this report.…”
Section: Introductionmentioning
confidence: 99%
“…Practical experience has shown that the straightforward solid‐state reaction of the elements in fused silica does not proceed in an easy way and requires careful handling, and the corresponding reaction for tungsten is ineffective. [18b] This prompted us to develop new methods for the preparation of W 6 I 12 and Mo 6 I 12 for subsequent ligand‐substitution reactions. At this point, we designed new compounds containing [M 6 I 8 L 6 ] 2– clusters (M = W, Mo) with various ligands (L).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a halide exchange reaction was developed by us, based on a facile reaction of WCl 6 with SiI 4 . The main product of this reaction is the tungsten iodide W 3 I 8 · 2I 2 7. This compound can be used to generate more tungsten iodide compounds that have not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%